Isolasi dan karakterisasi bakteri asam laktat dari susu sapi di Indonesia - Sugata, Marcelia; Layarda, Meiryanti; Chrislin, Ferren; Jan, Tan Tjie (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANA, 2024)
Cow's milk is a source of nutrition that has a good impact on health and contains a variety of microorganisms, one of which is lactic acid bacteria (LAB) such as Streptococcus thermophilus and Lactobacillus sp. Therefore, this study aimed to isolate and characterize LAB from the milk of Friesian Holstein dairy cows in Indonesia. In addition, BAL enumeration was carried out to determine the population of LAB in cow's milk samples. Based on the results obtained, as many as 4.36 log CFU/mL of LAB was successfully enumerated in the sample. Cell morphology observations showed that there were 15 Streptococcus, and 35 Lactobacillus candidate isolates which were Gram positive, did not form endospores, and did not have a wax coating on their cell walls. Furthermore, negative results of the catalase test were shown by 10 Streptococcus and 35 Lactobacillus candidate isolates. Carbohydrate fermentation test showed that isolate STRP1 and STRP4 were suspected to be Streptococcus sp., while the Lactobacillus isolates were possibly L. delbrueckii, L. acidophilus , and L. helveticus . The hemolytic test indicated that STRP1 is S. thermophilus with alpha hemolytic activity. Confirmation of the species of the isolates should be done through molecular identification and further characterization.